2016
DOI: 10.1093/cid/ciw626
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With Malaria Rapid Diagnostic Testing by Community Health Workers in 3 Malaria-Endemic Countries of Sub-Saharan Africa: An Observational Study

Abstract: Background. The World Health Organization recommends that all malaria management be based on parasitological identification. We monitored performance of trained community health workers (CHWs) in adhering to this recommendation to restrict artemisinin-based combination therapies (ACTs) to positive rapid diagnostic test (RDT)–confirmed cases in children in 3 malaria-endemic sub-Saharan African countries.Methods. In 33 villages in Burkina Faso, 45 villages in Nigeria, and 84 villages in Uganda, 265 CHWs were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
5
15
0
1
Order By: Relevance
“…The benefits of intensive supervision and coaching may also explain why such a low proportion of RDT-negative cases were incorrectly treated with ACT (1.2%). This rate is comparable with a recent study in three stable malaria-endemic sub-Saharan African countries that found that CHWs treated 1.03% of RDT-negative cases with ACT [ 19 ]. Most cases of incorrect treatment of RDT negative cases with ACT seemed to be by a few individual CHWs.…”
Section: Discussionsupporting
confidence: 88%
“…The benefits of intensive supervision and coaching may also explain why such a low proportion of RDT-negative cases were incorrectly treated with ACT (1.2%). This rate is comparable with a recent study in three stable malaria-endemic sub-Saharan African countries that found that CHWs treated 1.03% of RDT-negative cases with ACT [ 19 ]. Most cases of incorrect treatment of RDT negative cases with ACT seemed to be by a few individual CHWs.…”
Section: Discussionsupporting
confidence: 88%
“…Very few RDT-negative uncomplicated episodes (0.2% [29/12 656]) were treated with ACTs [13]. In a small number of patients (0.87% [139/15 932]), RDT diagnosis either was not done or results were not documented.…”
Section: Resultsmentioning
confidence: 99%
“…At a regional level, a multi-country study conducted in three West African countries, including Burkina Faso, showed an overall noncompliance rate below 1% in a small proportion (6.8%) of the community health workers (CHWs) involved. The lowest error rate was observed in CHWs working in Burkina Faso [64].…”
Section: Discussionmentioning
confidence: 83%